Sialis navasi, a new alderfly species from China (Megaloptera: Sialidae) - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2009)
The taxonomic position and synonymy of 11 native afrotropical species of Odontolochini Stebnicka & Howden, 1996 are discussed and re-descriptions are provided. Lectotypes are here designated for Odontolochus sulcatus Endrödi, 1964 and Loeblietus sulcatus Endrödi, 1979. The genus Loeblietus Endrödi, 1973 is formally synonymized with Odontolochus Schmidt, 1916 and seven new species level synonyms are proposed: Odontolochus chevalieri Paulian, 1942 syn. n., O. parcepunctatus Petrovitz, 1956 syn. n., O. sulcatus Endrödi, 1964 syn. n., and Loeblietus sulcatus Endrödi, 1979 syn. n. are found to be junior synonyms of O. raffrayi Paulian, 1942. Odontolochus granulipennis Petrovitz, 1956 syn. n. and O. heyrovskyi Balthasar, 1963 syn. n. are considered conspecific with O. spinicollis (Harold, 1871) and Odontolochus elgonensis Balthasar, 1961 syn. n. conspecific with O. oberthueri (Clouët, 1900). The name Anodontolochus Paulian, 1942 is determined to be unavailable as no type species was designated with the original description. A key to the 11 species of Odontolochus is provided, sexual dimorphic characters are described and illustrated for the first time, and a general diagnosis of the tribe on the world basis is included.